EFEKTIFITAS PENGGUNAAN WAYGROUND DALAM MENINGKATKAN HASIL BELAJAR MATERI TEKS NARASI PESERTA DIDIK KELAS III UPTD SDN MORKEPEK - Syaikhan Aufi Ardiansyah; Moh. Khoiron Jaza; Frendy Trianza; Ika Dian Rahmawati (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
The use of Wayground media in learning narrative texts needs to be tested for its effectiveness on the learning outcomes of third grade students at UPTD SDN Morkepek. This study aims to analyze the effectiveness of using the Wayground application to improve narrative text learning outcomes in third grade students at UPTD SDN Morkepek. The method used is quantitative with a one group pre-test post-test design. The sample consisted of 39 students taken using a saturated sampling technique. Data collection instruments included tests, semi structured interviews, and observation sheets. Data analysis was carried out interactively through data reduction, data presentation, and conclusion drawing. The results showed that the average pre-test score of students was 62.4, while the average post-test score increased to 76.8. Learning mastery based on the minimum mastery criterion of 70 increased from 56.41 percent in the pre-test to 82.05 percent in the post-test. Observations also showed that students were enthusiastic and actively engaged during learning using Wayground. Thus, the use of Wayground is proven effective in improving student learning outcomes in narrative text material. This study recommends Wayground as an interactive gamification based learning media in elementary schools.